Muscle as an osteoinductive niche for local bone formation with the use of a biphasic calcium sulphate/hydroxyapatite biomaterial. Issue 10 (October 2016) - Raina, D. B.; Gupta, A.; Petersen, M. M.; Hettwer, W.; McNally, M.; Tägil, M.; Zheng, M-H.; Kumar, A.; Lidgren, L.
Abstract : Objectives: We have observed clinical cases where bone is formed in the overlaying muscle covering surgically created bone defects treated with a hydroxyapatite/calcium sulphate biomaterial. Our objective was to investigate the osteoinductive potential of the biomaterial and to determine if growth factors secreted from local bone cells induce osteoblastic differentiation of muscle cells. Materials and Methods: We seeded mouse skeletal muscle cells C2C12 on the hydroxyapatite/calcium sulphate biomaterial and the phenotype of the cells was analysed. To mimic surgical conditions with leakage of extra cellular matrix (ECM) proteins and growth factors, we cultured rat bone cells ROS 17/2.8 in a bioreactor and harvested the secreted proteins. The secretome was added to rat muscle cells L6. The phenotype of the muscle cells after treatment with the media was assessed using immunostaining and light microscopy. Results: C2C12 cells differentiated into osteoblast-like cells expressing prominent bone markers after seeding on the biomaterial. The conditioned media of the ROS 17/2.8 contained bone morphogenetic protein-2 (BMP-2 8.4 ng/mg, standard deviation (sd ) 0.8) and BMP-7 (50.6 ng/mg, sd 2.2). In vitro, this secretome induced differentiation of skeletal muscle cells L6 towards an osteogenic lineage. Conclusion: Extra cellular matrix proteins and growth factors leaking from a bone cavity, along with a ceramic biomaterial, can synergistically enhance the process of ectopic ossification. The overlaying muscle acts as an osteoinductive niche, and provides the required cells for bone formation. Cite this article: D. B. Raina, A. Gupta, M. M. Petersen, W. Hettwer, M. McNally, M. Tägil, M-H. Zheng, A. Kumar, L. Lidgren. Muscle as an osteoinductive niche for local bone formation with the use of a biphasic calcium sulphate/hydroxyapatite biomaterial. Bone Joint Res 2016;5:500–511. DOI: 10.1302/2046-3758.510.BJR-2016-0133.R1.